Table of contents, editorial board, and other front matter - Leighton G. Watson (Journal of Applied Communications, 1974)
Editorial front matter and table of contents for vol.5 7, no.3, July-Sept. 1974 of ACE, the official Journal of the American Association of Agricultural College Editors.